Pemanfaatan Openwrt Sebagai Wifi Portable Dalam Pengembangan Jaringan Komunitas: Akses Internet Yang Terjangkau Dan Stabil - Ayatulloh Al Kursi; Kukuh Yudhistiro (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
This research aims to enhance internet access in rural areas by utilizing OpenWRT technology as a portable Wi-Fi. A case study was conducted in Bulupitu Village, Gondanglegi District, Malang Regency. The STB HG680P device was converted into a router with OpenWRT firmware (Helmiwrt), using non-regular internet packages such as ilmupedia. The results indicate that this system successfully provides stable and affordable internet access, with good signal strength and adequate internet speed. Positive impacts are observed in the improvement of accessibility, productivity, and social connectivity within the community. Challenges such as signal range limitations in enclosed areas are addressed through the use of additional repeaters and device maintenance training for network managers. This research provides a replicable model for other rural areas and offers practical solutions that can be widely implemented.